The Extent of the Utilization of Fruit and Vegetable Peel Waste Treatment into a Generic Wound Medicine - Corrharti Zooolaf (Community Service Akseprin Journal, 2024)
The majority of waste in the form of food scraps is a serious problem today, because it rots quickly and gives an unpleasant smell when inhaled. Global data shows that fruit and vegetable waste is the largest contributor to the world's food waste. It turns out that organic waste also has an environmental impact if not managed properly, such as producing harmful gases such as methane gas. The explosion incident at the Final Landfill is a poor example of organic waste management and producing methane gas. To overcome this, organic waste is generally processed into compost, but it is less known that organic waste, especially fruits and vegetables, can be used as natural wound healers through eco enzymes. Therefore, the service team assists housewives in Semarang in processing organic waste into eco enzymes that can help heal wounds, including in diabetics. This activity was carried out for 6 months, involving preparation, procurement of materials, assistance in making eco enzymes, monitoring, socialization, and evaluation. The results of the evaluation showed that participants were able to process organic waste into eco enzymes that are useful as natural wound healers, which can help diabetics. This is a positive step in sustainable waste management while helping those in need of better wound healing